Environmental Considerations in Aircraft Manufacturing Industry Through the Example of Boeing Andairbus Companies - Mezei, Balázs; Boros, Norbert (International Journal of Engineering and Management Sciences, 2016)
Aircraft manufacturing industry has developed dynamically in the last decades. Reinforced polymers have become the most dominant raw materials, while the recycling rate of the generated industrial waste has also increased. The fuel efficiency of the engines has increased, and the emitted CO2 per capita has significantly fallen. However, the environmental impact of the aircraft manufacturing industry seems to reach a permanent level. In this study, we have analyzed the environmental impact and the environmental considerations of the aircraft manufacturing industry through the examples of Boeing and Airbus companies. Our goal was to determine the relation between industrial growth and the environmental impact, particularly to the potential innovations.